2017
DOI: 10.1016/j.jalz.2017.06.1532
|View full text |Cite
|
Sign up to set email alerts
|

[P3–317]: DHA BRAIN UPTAKE AND APOE4 STATUS: A PET STUDY WITH [1‐11C]‐DHA

Abstract: Background: The apolipoprotein E ɛ4 (APOE4) allele is the strongest genetic risk factor identified for developing Alzheimer's disease (AD). Among brain lipids, alteration in the ω-3 polyunsaturated fatty acid docosahexaenoic acid (DHA) homeostasis is implicated in AD pathogenesis. APOE4 may influence both brain DHA metabolism and cognitive outcomes. Methods: Using positron emission tomography, regional incorporation coefficients (k*), rates of DHA incorporation from plasma into the brain using [1-11 C]-DHA (J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…In terms of PLs, Söderberg et al 116 found that the mean global gray matter DHA incorporation coefficient was 16% higher in APOE4 carriers vs non-carriers . A higher DHA incorporation coefficient was also observed in other regions including the entorhinal cortex 121 . However, the whole-brain DHA incorporation rate was not significantly different between APOE groups 121 .…”
Section: Modifications Of Brain Content During Agingmentioning
confidence: 57%
See 2 more Smart Citations
“…In terms of PLs, Söderberg et al 116 found that the mean global gray matter DHA incorporation coefficient was 16% higher in APOE4 carriers vs non-carriers . A higher DHA incorporation coefficient was also observed in other regions including the entorhinal cortex 121 . However, the whole-brain DHA incorporation rate was not significantly different between APOE groups 121 .…”
Section: Modifications Of Brain Content During Agingmentioning
confidence: 57%
“…A higher DHA incorporation coefficient was also observed in other regions including the entorhinal cortex 121 . However, the whole-brain DHA incorporation rate was not significantly different between APOE groups 121 . They also did not observe any age-related effects on DHA incorporation, but this may be due to the fact that only 4 of their 23 participants were over 50 years old 121 .…”
Section: Modifications Of Brain Content During Agingmentioning
confidence: 57%
See 1 more Smart Citation
“…Aldullah et al also reported a similar higher ARA: DHA ratio in PC and lyso-PC in hAPOE4 mice compared to hAPOE3 mice supporting that this mice model also have an imbalance in DHA and ARA compartment packaging (Abdullah et al, 2017). In ∼35 year-old humans, a positron emission tomography study with [1-11 C]-DHA reported however, that the mean global gray matter incorporation of DHA in the brain of E4 carriers was 16% higher than in non-carriers (Yassine et al, 2017). This higher uptake was particularly emphasized in the entorhinal region, an area affected early in AD pathogenesis and it was suggested by the authors it might represent a compensatory mechanism in younger E4 carriers to cope with increased brain DHA loss thus to maintain brain DHA levels (Yassine et al, 2017).…”
Section: Evidence Of Effective Prevention Strategiesmentioning
confidence: 82%
“…In ∼35 year-old humans, a positron emission tomography study with [1-11 C]-DHA reported however, that the mean global gray matter incorporation of DHA in the brain of E4 carriers was 16% higher than in non-carriers (Yassine et al, 2017). This higher uptake was particularly emphasized in the entorhinal region, an area affected early in AD pathogenesis and it was suggested by the authors it might represent a compensatory mechanism in younger E4 carriers to cope with increased brain DHA loss thus to maintain brain DHA levels (Yassine et al, 2017). Therefore, at younger ages, E4 carriers might require more DHA than non-carriers to support brain DHA turnover and prevent accumulation of Ab peptide since it was shown that higher plasma DHA levels were inversely associated to the brain Ab load (Yassine et al, 2016).…”
Section: Evidence Of Effective Prevention Strategiesmentioning
confidence: 99%